Perinatal programming of hypertension on exposure to high and low sodium chloride diet during pregnancy and lactation in Sprague-Dawley rats - Aminuddin, Niferiti; Abdul Razak, Tariq; Azzubaidi, Marwan Saad; Tin, Myo Han; Mohd Noor, Noriah (2014)
Background: Adverse conditions in utero may lead to hypertension during in later life, however inconsistency of the result has been reported.